Предмет: Математика,
автор: vagekirakosyan1
a) (4+a)^2
б) (2x-1)^2
в) (2a+3b)^2
г) (x^3-3)^2
Решите пожалуйста очень надо бы
Заранее спасибо
Ответы
Автор ответа:
0
(2x-1)^2=(2x)^2-2*2x+1=4x^2-4x+1
(2a+3b)^2=4a^2+2*2a*2b+9b^2=4a^2+8ab+9b^2
(x^3-3)^2=(x^3)^2-2*x^3*3+3^2=x^5-18x-9
(2a+3b)^2=4a^2+2*2a*2b+9b^2=4a^2+8ab+9b^2
(x^3-3)^2=(x^3)^2-2*x^3*3+3^2=x^5-18x-9
Похожие вопросы
Предмет: Математика,
автор: pbohrg
Предмет: Английский язык,
автор: aidanaaaa4
Предмет: Геометрия,
автор: djetpisovp5h0v3
Предмет: Математика,
автор: vikamikhaleva
Предмет: Математика,
автор: Svetoscopy2011